ASSESSMENT MODEL FOR SUSTAINABLE RURAL DEVELOPMENT AT NUTS 3 LEVEL: A MULTI-CRITERIA APPROACH - Jež Rogelj, Mateja; Mikuš, Ornella; Hadelan, Lari (Economics of Agriculture, 2024)
Sustainable rural development, encompassing economic growth, social equity, and environmental protection, is a multifaceted concept with inherent complexities. Achieving it often involves navigating trade-offs between these three pillars. To effectively allocate resources and achieve convergent development in the EU, measuring rural sustainability at the regional level is crucial. The multicriteria approach addresses this challenge by considering the diverse perspectives of stakeholders involved in rural development. This paper presents a model for measuring sustainable rural development at the NUTS 3 level in Croatia, utilizing the Analytic Hierarchy Process (AHP) within a multi-criteria analysis framework. Based on a survey of rural development stakeholders, 15 indicators were selected, weighted, and incorporated into the model. The survey revealed that economic indicators received the highest weight (0.415), followed by social (0.309) and environmental (0.275) considerations. This model offers a valuable foundation for local and regional decision-makers to develop strategies and implement actions that promote sustainable development in rural areas.